Barrier protective effects of asiatic acid in TNF-α-induced activation of human aortic endothelial cells - Lai, Yen Fong; Chin, Theng Ng; Zhi, Li Cheok; Mohd Moklas, Mohamad Aris; Hakim, Muhammad Nazrul; Ahmad, Zuraini (Elsevier, 2016)
Background: Endothelial cell activation is characterized by increased endothelial permeability and increased expression of cell adhesion molecules (CAMs). This allows monocyte adherence and migration across the endothelium to occur and thereby initiates atherogenesis process. Asiatic acid is a major triterpene isolated from Centella asiatica (L.) Urban and has been shown to possess anti-oxidant, anti-hyperlipidemia and anti-inflammatory activities.